2023
DOI: 10.1101/2023.03.06.531323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and functional properties of the transporter SLC26A6 reveal mechanism of coupled anion exchange

Abstract: Members of the SLC26 family constitute a conserved family of anion transport proteins, which encompasses uncoupled transporters with channel-like properties, coupled exchangers and motor proteins. Among the eleven paralogs in humans, several participate in the secretion of bicarbonate in exchange with chloride and thus play an important role in pH homeostasis. Previously, we have elucidated the structure of murine SLC26A9 and defined its function as an uncoupled chloride transporter (Walter, Sawicka, & Dut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…This observation is in line with a recent report that R404V conferred a small, uncoupled chloride transport function on SLC26A6 (Tippett et al, 2023).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is in line with a recent report that R404V conferred a small, uncoupled chloride transport function on SLC26A6 (Tippett et al, 2023).…”
Section: Resultssupporting
confidence: 93%
“…1 , left), SLC26A5 (Bavi et al, 2021; Butan et al, 2022; Futamata et al, 2022; Ge et al, 2021) ( Fig. 1 , middle), SLC26A6 (Tippett et al, 2023), and SLC26A9 (Chi et al, 2020; Walter et al, 2019) ( Fig. 1 , right).…”
Section: Resultsmentioning
confidence: 99%
“…A recent cryo-EM study on mouse pendrin (Liu et al, 2023) revealed a homodimeric architecture that is similar to prestin (Bavi et al, 2021; Butan et al, 2022; Futamata et al, 2022; Ge et al, 2021) and other SLC26 proteins (Chi et al, 2020; Tippett et al, 2023; Walter et al, 2019). The transmembrane domain consists of the gate and the core domains, and the ion translocation pathway is located in between them ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SLC26 anion exchangers form dimeric assemblies that can be demonstrated by structural studies (22,(43)(44)(45)(46)(47)(48) as well as by native gel electrophoresis (49). Since both experimental approaches do not exclude formation of higher oligomers, which are not sufficiently stable to tolerate solubilization/purification, we recently used a new dual-color colocalization (DCC) approach for the accurate determination of subunit stoichiometries of membrane proteins in situ (50,51).…”
Section: Discussionmentioning
confidence: 99%